Physics-based control of neoclassical tearing modes on TCV. (1st April 2022) - Kong, M; Felici, F; Sauter, O; Galperti, C; Vu, T; Ham, C J; Hender, T C; Maraschek, M; Reich, M; et al.
Abstract: This paper presents recent progress in studies of neoclassical tearing modes (NTMs) on TCV, concerning the new physics learned and how this physics contributes to a better real-time (RT) control of NTMs. A simple technique that adds a small (sinusoidal) sweeping to the target electron cyclotron (EC) beam deposition location has proven effective both for the stabilization and prevention of 2 / 1 NTMs. This relaxes the strict requirement on beam-mode alignment for NTM control, which is difficult to ensure in RT. In terms of the EC power for NTM stabilization, a control scheme making use of RT island width measurements has been tested on TCV. NTM seeding through sawtooth (ST) crashes or unstable current density profiles (triggerless NTMs) has been studied in detail. A new NTM prevention strategy utilizing only transient EC beams near the relevant rational surface has been developed and proven effective for preventing ST-seeded NTMs. With a comprehensive modified Rutherford equation (co-MRE) that considers the classical stability both at zero and finite island width, the prevention of triggerless NTMs with EC beams has been simulated for the first time. The prevention effects are found to result from the local effects of the EC beams (as opposed to global current profile changes), as observed in a group of TCV experiments scanning the deposition location of the preemptive EC beam. The co-MRE has also proven able to reproduce well the island width evolution in distinct plasma scenarios on TCV, ASDEX Upgrade and MAST, with very similar constant coefficients. The co-MRE has the potential to be applied in RT to provide valuable information, such as the EC power required for NTM control with RT-adapted coefficients, contributing to both NTM control and integrated control with a limited set of actuators.